Attenuated Legionella pneumophila Survives for a Long Period in an Environmental Water Site. (3rd July 2019) - Nishida, Takashi; Nakagawa, Natsuko; Watanabe, Kenta; Shimizu, Takashi; Watarai, Masahisa
Abstract : Legionella pneumophila is known as a human pathogen and is ubiquitous in natural and artificial aquatic environments. Many studies have revealed the virulence traits of L. pneumophila using clinical strains and a number of studies for characterizing environmental strains are also reported. However, the association between the virulence and survivability in the environment is unclear. In the present study, L. pneumophila was isolated from environmental water sites (Ashiyu foot spa, water fountain, and public bath), and the serogroups of isolated strains were determined by serological tests. Isolated strains were found to belong to serogroups SG1, SG2, SG3, SG4, SG5, SG8, SG9, and SG13. Untypeable strains were also obtained. Isolated strains were used for intracellular growth assay in a human monocytic cell line, THP-1. Among these strains, only an untypeable strain, named AY3, failed to replicate in THP-1. In addition, AY3 was maintained for a long period in an environmental water site, Ashiyu foot spa 2. Further, we compared the characteristics of several strains isolated from Ashiyu foot spa 2 and a clinical strain, Togus-1. AY3 failed to replicate in THP-1 cells but replicated in an amoeba model, Dictyostelium discoideum . Compared with Togus-1, the culturable cell number of environmental strains under stress conditions was higher. Moreover, biofilm formation was assessed, and AY3 showed the same degree of biofilm formation as Togus-1. Biofilm formation, replication in amoebae, and resistance against stress factors would explain the predominance of AY3 at one environmental site. Although the mechanism underlying the difference in the ability of AY3 to replicate in THP-1 cells or amoebae is still unclear, AY3 may abandon the ability to replicate in THP-1 cells to survive in one environment for a long period. Understanding the mechanisms of L. pneumophila in replication within different hosts should help in the control of Legionnaires' disease, but further study is necessary.